Competence and Perceived Benefits in Project-Based Learning for Postgraduate Students in History Education - Kurniawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2021)
The paradigm developed at the State University of Jakarta (UNJ) in recent years has focused on competence to achieve workability. This paradigm shift requires a more flexible and active teaching-learning context. This paper presents empirical research into the application of a case-based project-based learning model (Case-Project Based Learning, CPjBL) in the learning of Evaluation, Process, and Learning Outcomes courses at the History Education Postgraduate Program of UNJ. Considering the important role of motivation and performance, we pursue three main goals. First, this study aims to analyze students' perceptions of the effectiveness of the CPjBL learning model to improve key competencies for employability. Second, we explored whether the perceived benefits of these competencies changed after the PBL trial. Finally, we aim to explore students' opinions about the usefulness, advantages, and disadvantages of this model. Our findings support the perceived effectiveness of PBL for improving teamwork, communication, creativity, organization, and information management competencies.